2022
DOI: 10.2166/wp.2022.190
|View full text |Cite
|
Sign up to set email alerts
|

Research on water resources pricing model under the water resources–economic high-quality development coupling system: a case study of Hubei Province, China

Abstract: Achieving high-quality economic development under the new development pattern has become an inevitable requirement for China's economic development. Correctly calculating the value of water resources and optimizing the price mechanism of water resources is one of the important guarantees for promoting the high-quality development of the regional economy. Based on this fact, this paper takes Hubei Province as an example to construct a coupling relationship model between water resources and economic high-quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Regarding the evaluation of high-quality development, most scholars use evaluation methods such as the entropy weight method [11,[22][23][24] and TOPISI method [25,26] to construct evaluation index systems and calculate the level of high-quality development, and a few scholars use methods such as DEA model [27] and coupling coordination degree analysis [28][29][30] to evaluate the development of regions with high quality. In addition, some scholars have conducted comparative studies on the relationship and differences between high-quality development and sustainable development, believing that early high-quality development was more focused on economic quality compared to sustainable development [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding the evaluation of high-quality development, most scholars use evaluation methods such as the entropy weight method [11,[22][23][24] and TOPISI method [25,26] to construct evaluation index systems and calculate the level of high-quality development, and a few scholars use methods such as DEA model [27] and coupling coordination degree analysis [28][29][30] to evaluate the development of regions with high quality. In addition, some scholars have conducted comparative studies on the relationship and differences between high-quality development and sustainable development, believing that early high-quality development was more focused on economic quality compared to sustainable development [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This integrated approach reflects a balanced relationship between environmental protection and economic benefits under a differentiated sewage treatment fee system. Therefore, it is suggested that different regions adopt different sewage treatment fee collection standards based on their respective economic development levels and current environmental quality conditions [78][79][80][81], whereby higher pollution would lead to higher fees.…”
Section: Implementing a Differentiated Sewage Treatment Fee Collectio...mentioning
confidence: 99%
“…China is one of the main countries in the world with inadequate water resources, with per capita water resources of only 2074.53 m 3 [4]. Moreover, with the rapid development of industrialization and urbanization, the demand for water resources is increasing [5,6]. Consequently, China is currently facing a serious problem with sustainable water use.…”
Section: Introductionmentioning
confidence: 99%